Strategi Pembelajaran Berbasis Multiple Intelegence Menurut Munif Chatib Pada Sekolah Dasar - Ahmad Noviansah (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this writing, focus discusses the concept of the Intelegence Munif Khatif in Basic. This research uses the type of research literature (library reseach) with a qualitative research approach. The data collection techniques in this study are documentation studies, analysis is done by comparing and combining documents. The data source used is the books and journals associated with the selected topic. The data analysis technique used in this research is a content analysis method in obtaining valid inference in this analysis, the process of selecting, comparing, combining, sorting through various understandings, to the relevant found. The results of the research of Munif Chatib in the learning of multiple intelligences based on 3 important activities, namely: 1) Input stage, commonly done by doing MIR (Multiple Intelligences Research) in the acceptance of his new students; 2) Stages in the learning process, where the teaching style of the teacher must be the same as the learning style of the participants, Munif divide into 4 stages: (Brain, teaching strategy, products, and Benefit); and 3) Output, at this stage an authentic assessment is an assessment of a learner, an authentic assessment that shoots three spheres of cognitive, affective and psychomotor